INTERNATIONAL BUSINESS NEGOTIATION. BARGAINING POWER AND ITS IMPACTS ON THE OUTCOMES OF INTERNATIONAL BUSINESS NEGOTIATIONS BETWEEN IOCs AND HOST GOVERNMENTS. A CASE OF SHELL AND IRAQI GOVERNMENT - THAI, PHUONG (2012)
Nowadays, thanks to development in technology and transportation, globalisation becomes inevitable. As a part of globalising process, companies search for new opportunities overseas. In order to utilise those opportunities, foreign companies need the help of local businesses in order to familiarise themselves to the new markets. Hence, negotiations take places to reach desirable division of gain for foreign and local companies/host governments. This process is also called international business negotiation. Within oil and gas industry, international business negotiation happens often between international oil companies and host governments because of unequal distribution of oil and gas reserves around the world. The outcomes of negotiations between IOCs and host governments are depended on who have more bargaining power. Bargaining power of IOCs come from their resources such as technology, finance and managerial skills. If these resources are very unique then the bargaining power of IOCs could be sustained even after their entry point negotiation. On the other hands, the bargaining power of host governments come from their oil and gas resources, economic and politic conditions of their countries. There are also constraints to IOCs and host governments’ bargaining power such as their legitimacy, previous contracts and lobbying. In order to create efficient negotiation strategies to get the best outcomes, IOCs and host governments need to understand their and other involved parties’ bargaining power. The $17bn gas deal between Shell and Iraqi was chosen to be evaluated in this dissertation because of three reasons. Firstly, this is the biggest gas deal for Iraq after the 2003, which promises to supply enough gas to run electricity generators in Iraq and open access to international market for Iraq gas in the future. Secondly, this is the first step for Iraq to rebuild its economy. Lessons should be learned for future contracts. Thirdly, the case has all the characteristics of all international business negotiation that could be illustrated the theories of bargaining power. Overall, the results of negotiation between and Iraqi government benefit Shell because Shell has more bargaining power compared to Iraqi government.